Peran Media Sosial sebagai Sarana Pengembangan Kompetensi Lintas Budaya Mahasiswa - Ni Luh Kadek Rustiawati; Rizkahulmiftah Rizkahulmiftah; I Wayan Mudana; Ida Bagus Made Astawa; I Made Pageh (Universitas Hamzanwadi, 2026)
This study was motivated by the high use of social media among university students, which has the potential to support the development of cross-cultural competence in the digital era. Cross-cultural competence is an essential skill that enables students to interact effectively in an increasingly diverse society. This study aims to describe the level of social media utilization, the level of students’ cross-cultural competence, and the role of social media as a medium that supports the development of cross-cultural competence. A descriptive quantitative approach was employed with a sample of 79 students selected through convenience sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics through mean and percentage calculations. The findings revealed that social media utilization was categorized as high with a mean score of 3.94, while students’ cross-cultural competence was also categorized as high with a mean score of 4.02. The highest indicator of social media utilization was the use of social media to obtain information about other cultures (4.24), whereas the highest indicator of cross-cultural competence was respect for cultural differences (4.39). The findings indicate that social media has the potential to serve as a learning resource that supports the expansion of cultural awareness, strengthens appreciation of diversity, and enhances students’ readiness to interact with individuals from different cultural backgrounds. The study implies the importance of utilizing social media as a learning medium to strengthen multicultural values in Social Studies Education.